Metformin: time to review its role and safety in chronic kidney disease. Issue 1 (12th June 2019) - Tanner, Cara; Wang, Gayathiri; Liu, Nancy; Andrikopoulos, Sofianos; Zajac, Jeffrey D; Ekinci, Elif I
Summary: ■ Metformin is recommended as first‐line therapy for type 2 diabetes because of its safety, low cost and potential cardiovascular benefits. ■ The use of metformin was previously restricted in people with chronic kidney disease (CKD) — a condition that commonly coexists with diabetes — due to concerns over drug accumulation and metformin‐associated lactic acidosis. ■ There are limited data from observational studies and small randomised controlled trials to suggest that metformin, independent of its antihyperglycaemic effects, may be associated with lower risk of myocardial infarction, stroke and all‐cause mortality in people with type 2 diabetes and CKD. ■ Research into the risk of metformin‐associated lactic acidosis in CKD has previously been limited and conflicting, resulting in significant variation across international guidelines on the safe prescribing and dosing of metformin at different stages of renal impairment. ■ Present‐day large scale cohort studies now provide supporting evidence for the safe use of metformin in mild to moderate renal impairment (estimated glomerular filtration rate [eGFR] 30–60 mL/min/1.73m 2 ). However, prescribing metformin in people with severe renal impairment (eGFR < 30 mL/min/1.73m 2 ) remains a controversial issue. Due to observed increased risk of lactic acidosis and all‐cause mortality in people with type 2 diabetes and severe renal impairment, it is generally recommended that metformin is discontinued if renal function falls below this level or during acute renal deterioration.